Sustainability-linked bonds: is there greenium? - Bonacina, Luis Gustavo Ferreira (2022)
Why should companies issue Sustainability-Linked Bonds (SLBs)? Following Flammer (2021) and Tang and Zhang (2020), I test a potential rational for issuing SustainabilityLinked Bonds instead of a “Brown Bonds”. If Sustainability-Linked Bonds investors are willing to accept lower yields for the sake of a better world, Sustainability-Linked Bonds can represent a cheaper source of finance. To examine the cost of capital argument, for each Sustainability-Linked Bonds, I match an otherwise “Brown Bonds” by the same issuer. I run two different models of matching. The goal is ensures that the two bonds are as similar as possible. Then, I test whether the yield differential between the SLBs and the counterfactuals is significant. I analyze the difference with a parametric test, paired t-test, as well as with a non-parametric test, Wilcoxon Signed Rank Test. For the robustness of my results I perform a series of linear OLS regressions on the yield at issue with different sets of control variables. The results show that in both models, the cost of financing through SLBs is lower for the company. In model 1, the difference in yield on the issuance of SLBs is 36 bps to 54 bps lower than “Brown Bonds”. While in model 2, which has a smaller restriction between the years, the result also remains negative, ranging from 71 bps to 104 bps. These results are maintained in all tests performed.